2013
DOI: 10.1002/hep.25832
|View full text |Cite
|
Sign up to set email alerts
|

Resection of hepatocellular cancer ≤2 cm: Results from two Western centers

Abstract: Asian series have shown 5 year survival of ∼70% after resection of hepatocellular cancer (HCC) <2cm. Western outcomes with resection have not been as good. In addition ablation of HCC ≤ 2cm has been shown to achieve competitive results leaving the role of resection unclear in these patients. Records of patients undergoing resection at two Western centers between 1/1990 and 12/2009 were reviewed. Patients with a single HCC ≤ 2cm on pathology were included. Thirty clinical variables including demographics, liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
260
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(281 citation statements)
references
References 33 publications
(56 reference statements)
13
260
0
1
Order By: Relevance
“…The presence of splenomegaly (major diameter > 12 cm) or esophageal varices with a platelet count of < 100,000/mm 3 correlate with the same endpoints and are easier to identify [27] .…”
Section: Ng Standardmentioning
confidence: 98%
See 1 more Smart Citation
“…The presence of splenomegaly (major diameter > 12 cm) or esophageal varices with a platelet count of < 100,000/mm 3 correlate with the same endpoints and are easier to identify [27] .…”
Section: Ng Standardmentioning
confidence: 98%
“…Of the ava function [1, necrosis ge satellite les region of t ablation co to multifoc bolization optimal pat All treatm complicatio significanc tumor loca technique i confined v limitations [18,27] . There es supporting R dard of care f be clearly seen n the surround latest improve erstandable tha HCC > 3 cm, t m [45,46] .…”
Section: Radiofreqmentioning
confidence: 99%
“…1 The management of HCC has substantially changed in the past few decades. Earlier, HCC was treated by surgical resection, but multifocal HCC often arise synchronously or metachronously as new tumors or as intrahepatic metastases of the primary cancer, leading to high mortality rates in HCC patients [2][3][4] ; therefore, new strategies to treat HCC are needed in addition to the current therapies.…”
Section: Introductionmentioning
confidence: 99%
“…This issue of HEPATOLOGY publishes the result of a combined effort from two large referral centers, based in New York and Milan, 9 reporting on the outcomes and prognostic factors of surgical resection in patients with HCC <2 cm in diameter. In this large western series, survival at 5 years was 70% and was influenced by the presence of satellites and by platelet count, with the best results obtained in patients with more than 150,000 platelets (83% survival at 5 years).…”
mentioning
confidence: 99%
“…Roayaie et al also showed that at least one third of these early tumors present with microvascular invasion or satellites. 9 On the other hand, approximately 5% of these lesions turn out to be either benign lesion or hepatocholangiocarcinomas. 15 Thus, surgical resection has the advantage of confirming the diagnosis and providing important pathologic information that may affect the following treatment strategy (i.e., prevention of recurrence, indication, and timing for transplantation).…”
mentioning
confidence: 99%